TGM2 regulated by transcription factor NR3C1 drives p38 MAPK-mediated tumor progression and immune evasion in lung squamous cell carcinoma - Lin, Chunlong; Li, Shangfu; Yi, Liang; Zhou, Huiling; Xiao, Zhiyi; Yang, Zhuo; Chen, Qingping; Peng, Xiangyang; Li, Kanao; Wang, Qing; Liu, Wei; Li, Ni; et al. (Frontiers in Immunology, 2025)
BackgroundLung squamous cell carcinoma (LUSC) is highly malignant with limited therapeutic targets. Prior studies indicate transglutaminase 2 (TGM2) regulates the tumor microenvironment, but its mechanisms in driving LUSC progression and immune evasion remain unclear.MethodsThe prognostic value of TGM2 was analyzed using the TCGA LUSC cohort. Key genes were screened via random forest algorithm. Functional validation was performed in NCI-H520 and SK-MES-1 cell lines. Proteomics, GSEA, and TIMER2.0 assessed downstream pathways and immune infiltration. Transcriptional regulatory databases predicted the upstream transcription factors of TGM2, which was then validated by chromatin immunoprecipitation (ChIP)-qPCR.ResultsTGM2 was an independent prognostic factor for LUSC. High TGM2 expression correlated with reduced overall survival (OS, P = 0.00018) and disease-free survival (DFS, P = 0.00019). TGM2 promoted proliferation, migration, invasion, clonogenicity, and suppressed apoptosis in LUSC cells by activating p38 MAPK signaling. Elevated TGM2 levels were associated with an immunosuppressive microenvironment: decreased Th1 (R = -0.186, P < 0.0001) and NK cell infiltration (R = -0.116, P = 0.0092), and increased M2 macrophage (R = 0.164–0.528, P < 0.0001) and cancer-associated fibroblast infiltration (R = 0.469, P < 0.0001). NR3C1 was identified as a key transcription factor regulating TGM2. ChIP-qPCR analysis confirmed that NR3C1 binds to a specific site (921-935) within the TGM2 promoter, and their expression showed a strong positive correlation (R = 0.53, P < 0.0001).ConclusionTGM2 drives LUSC progression via p38 MAPK activation and shapes an immunosuppressive microenvironment, which is transcriptionally regulated by NR3C1. This study supports TGM2 as a prognostic biomarker and suggests its potential as a therapeutic target, which may inform future combination immunotherapy strategies.